The Effects of Role Breadth Self-Efficacy, Work Engagement and Organizational Justice as Moderators Changing the Relationships Between Talent Mindset Competency and Job Performance - Prasertkul, Siam; Piriyakul, Montree; Chinuntdej, Norapol; Hantrakul, Nattawut (Ph.D. in Social Sciences Journal, 2018)
In this dissertation, the researcher studies (1) talent mindset competency, job satisfaction, role breadth self-efficacy, work engagement, organizational justice, and job performance. (2) the influence of job satisfaction as a linking factor between talent mindset competency and job performance. (3) the influence of role breadth self-efficacy, work engagement, and organizational justice as moderators of the relationships between talent mindset competency and job performance. In this mixed-methods research investigation, the researcher collected germane data from a sample population of 629 private sector employees involved in the juristic person business. In the qualitative phase of this research inquiry, semi-structured in-depth interviews were carried out with nine administrators from the PTT Public Company Limited group (PTT). Findings of the quantitative research phase of investigation are as follows: 1. Findings job satisfaction; role breadth self-efficacy; work engagement; organizational justice; and job performance of private sector employees, the total Mean was evinced at a high level. But the talent mindset competency the total Mean displayed at a moderate level. 2. Findings of the influences linking job satisfaction with the talent mindset competency reduced the direct influence on job performance from 0.489 to 0.084. 3. It was indicated that work engagement and organizational justice were moderators displaying direct influence on the relationship between talent mindset competency and job performance at the statistically significant levels of 0.05 and 0.01, respectively. However, role breadth self-efficacy did not exhibit direct influence in this relationship.